Literacy Transformation in Junior High Schools Through the Book Writing Movement - Edhi Siswanto; Putri Robiatul Adawiyah; Budi Satria Bakti (Journal Of Humanities Community Empowerment, 2025)
The low level of literacy among Indonesian students, particularly in creative writing skills, remains a significant challenge in education. To address this issue, a community service program titled Book Writing Movement was implemented at SMP Muhammadiyah 2 Jember, aiming to promote students' productive literacy. The program consisted of two main stages: socialization and participant selection, followed by a creative writing workshop. Out of 40 students, 10 were selected based on interest and commitment to participate in a four-session intensive training. The workshop covered topics such as idea development, narrative writing structure, character building, language style, and basic editing. Results showed that 80% of participants were able to construct logically structured stories, and 70% demonstrated improvement in vocabulary and language style. On average, students' writing skills improved by 35%. Beyond cognitive gains, students also reported increased self-confidence and motivation to write independently. The program demonstrates that a structured, practice-based approach can effectively foster a culture of literacy in schools. For sustainability, it is recommended to provide ongoing mentorship, involve more students across grades, and engage teachers and publishers to support student publication